DFT modelling on the effect of manganese in cobalt-based FT-catalysts - Ragoo, Yatheshthrao (Department of Chemical Engineering, 2024)
The Fischer-Tropsch synthesis (FTS) process can be described as a combination of reactions that convert synthesis gas (essentially CO and H2) into long chain hydrocarbons (syncrude), which in turn is refined into transportation fuels, lubricants, and other petrochemicals. Among the commercially implemented catalysts such as Fe and Co, the latter is considered as a successful candidate for catalysing FTS reactions towards long chain hydrocarbons (C5+) primarily due to its high activity and longer lifespan. To further drive the selectivity towards longer chain hydrocarbons, manganese may be added to the cobalt-based catalyst as a promoter. To this date, experimental studies have suggested that Mn exists as MnOx in the working catalyst, and it has been proposed that manganese facilitates the dissociation of CO. To investigate the promotional effect of Mn, suitable DFT-based MnOx models were devised on the basis of their formation under Fischer-Tropsch conditions. These were modelled on the Co(111) surface owing to it being amongst the densest surface planes of cobalt. Thermodynamically, the OMn and O2Mn ligands, are the most likely form of Mn on a Co(111) surface under Fischer-Tropsch conditions with OMn being the ligand present at low ratios of H2O to H2 and O2Mn becoming the dominant species at high conversion. An essential feature of the Fischer-Tropsch synthesis is the adsorption and dissociation of adsorbed CO and the removal of surface oxygen. The presence of the dominant forms of the manganese complex (OMn and O2Mn) on Co(111) on these reaction steps was probed. It was found that the presence of OMn on Co(111) stabilised the adsorption of CO further and both the presence of OMn and O2Mnduces an elongation of the C-O bond in adsorbed CO. The presence of OMn also stabilises the dissociation products, co-adsorbed carbon and oxygen on Co(111), whereas the presence of O2Mn does not seem to affect the dissociation equilibrium significantly. The presence of these ligands slightly enhances the rate of dissociation of CO by lowering the barrier for CO-dissociation from 2.59 eV on Co(111) to 2.55 eV in the presence of OMn and to 2.37 eV in the presence of O2Mn. Hence, the presence of MnOx on Co(111) results in a slightly faster direct CO dissociation than on a clean slab. It should however be noted that the direct CO-dissociation on Co(111) is very slow at typical Fischer-Tropsch conditions, even in the presence of MnOx ligands. Hence, hydrogen-assisted CO dissociation is typically considered on these dense surfaces. The hydrogen assisted CO-dissociation over Co(111) proceeds with an activation barrier of 0.18 eV. The presence of MnOx ligands does not seem to facilitate the hydrogen-assisted dissociation based on the pathways considered as elevated barriers were determined. The disproportionation of surface hydroxyl species was considered as the key reaction for the removal of surface oxygen as water, and the systems involving the precursors of the reaction were compared. The presence of MnOx ligands on Co(111) offers new pathways for oxygen removal involving hydroxylated surface manganese complexes, i.e., OMn(OH) and O2Mn(OH), which can act as reactive intermediates in the oxygen removal. A microkinetic analysis shows that the oxygen removal in the presence of O2Mn on Co(111) was ca. 104.2 times faster than in the absence of this ligand under Fischer-Tropsch conditions. It is thus concluded that manganese as a promoter for cobalt-based catalysts may affect the CO adsorption but may not affect the dominant indirect hydrogen assisted CO-dissociation. The promotional effect of manganese may be related to the oxygen removal from Co(111)